MicroRNAs in the diagnosis, prognosis and treatment of cancer - Violaine Havelange; Catherine E.A. Heaphy; Ramiro Garzon (Frontiers Media S.A., 2011)
MicroRNAs (miRNAs) are small non-coding RNAs that regulate critical cell processes such as cell proliferation, apoptosis and differentiation by modulating gene expression. MiRNAs deregulation has been observed extensively in cancer. Elegant studies have demonstrated that miRNAs are involved in the initiation and progression of several malignancies. In this review we will address the role of miRNAs in the diagnosis and prognosis of cancer. The development of new drugs mimicking or blocking miRNAs will be discussed.